Want to improve return to sport outcomes following injury? Empower, engage, provide feedback and be transparent: 4 habits! - King, J.; Roberts, C.; Hard, S.; Ardern, C. L. (British Journal of Sports Medicine, 2019)
A major limitation of the traditional return to sport (RTS) decision has been the exclusion of the athlete in question. Recently, two frameworks have underscored the importance of involving the athlete in a multidisciplinary team (MDT) and putting them at the centre of a shared decision-making process that collectively decides RTS protocol. RTS should also be considered as a continuum that begins at the onset of injury, rather than an isolated step occurring at the end of rehabilitation. It should be a process that fosters athlete autonomy; this has been shown to promote personal development, improve motivation and task performance, and subsequently improve rehabilitation outcomes.